Increased indole detection for Pasteurella multocida. - Clemons, K V (1982)
A supplemented 2% peptone broth is described for the detection of indole production by Pasteurella multocida. The 96 isolates of P. multocida that were utilized in this evaluation were indole positive within 18 to 24 h.